2021
DOI: 10.7759/cureus.14521
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sugammadex on Prothrombin and Activated Partial Thromboplastin Time

Abstract: Sugammadex is routinely used as an effective neuromuscular blockade reversal agent. Several studies have indicated that it may prolong the prothrombin time (PT) and the activated partial thromboplastin time (aPTT). This review gathers the relevant in vivo studies to accumulate knowledge on the subject. Nine studies were included. According to the results, sugammadex seems to lead to a transient increase in aPTT and PT values, compared to standard care. However, the clinical impact seems to be trivial. Neverthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…3 The selective relaxant binding agent sugammadex has demonstrated to effectively and quickly restore neuromuscular function from a neuromuscular blockade by rocuronium or vecuronium. 4 However, it may increase a risk of postoperative bleeding due to its anticoagulatory effect 5 or a risk of hypersensitivity reactions and anaphylaxis. 6 Although anaphylaxis and coagulation abnormalities with sugammadex are indeed a problem, they are infrequent and sugammadex can be used safely in most cases.…”
Section: Introductionmentioning
confidence: 99%
“…3 The selective relaxant binding agent sugammadex has demonstrated to effectively and quickly restore neuromuscular function from a neuromuscular blockade by rocuronium or vecuronium. 4 However, it may increase a risk of postoperative bleeding due to its anticoagulatory effect 5 or a risk of hypersensitivity reactions and anaphylaxis. 6 Although anaphylaxis and coagulation abnormalities with sugammadex are indeed a problem, they are infrequent and sugammadex can be used safely in most cases.…”
Section: Introductionmentioning
confidence: 99%
“…12,13,15,20 The increase seems to be dose-dependent and temporary, resolving after around 1 hour. 19 Consequently, no difference in RBC transfusion nor laboratory parameters has been demonstrated in surgical patients having a liver transplantation after 24 hours of sugammadex administration. 21 It has been further postulated that the prolongation in coagulation assays associated with sugammadex could be secondary to an in vitro artifact by an apparent phospholipid-binding effect.…”
Section: Discussionmentioning
confidence: 99%
“…18 The initial concern that sugammadex may interfere with coagulation is based on early studies on coagulation laboratory parameters. 19 Multiple studies reported a prolongation of several coagulation parameters, especially aPTT and INR, after sugammadex application. 12,13,15,20 The increase seems to be dose-dependent and temporary, resolving after around 1 hour.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Additionally, sugammadex has been reported to cause QT prolongation, bradycardia, cardiac arrest, increased prothrombin time, and increased activated partial thromboplastin time. [17][18][19] Finally, recurrence of neuromuscular blockade can occur with lower sugammadex doses despite initial reversal. 17,19 These effects should be considered by providers when weighing the risks and benefits of neuromuscular blockade reversal.…”
Section: Discussionmentioning
confidence: 99%